1.5: Latino Studies en tránsito. Issue 4 (December 2016) - Decena, Carlos
Abstract Drawing on the metaphor of the "1.5 generation" in studies of immigration, Decena proposes it as "the moment" in the life cycle of Latino Studies as a field because of how it pushes us to attend to continuities and departures in pedagogically inspired scholarly practice. This reflexión advances the following claims: first, that while the need to "document" US Latino populations persists given our political climate, inquiries in the field have also begun to grapple with the multiple significations and investments for community formation, institution-building and state regulation that pivot the term Latino; second, that movements to "document" or move away from documentary efforts in Latino Studies respond to the uneven influence of Latino Studies in traditional disciplines; and finally, that intellectual questions raised by initial and contemporary views of US Latino populations challenge us to center and explore transnational linkages with Latin America, thus prompting engagements and intellectual travel between Latino and Latin American studies.